2020
DOI: 10.3390/ijms21113993
|View full text |Cite
|
Sign up to set email alerts
|

The Osmotin-Like Protein Gene PdOLP1 Is Involved in Secondary Cell Wall Biosynthesis during Wood Formation in Poplar

Abstract: Osmotin-like proteins (OLPs) mediate defenses against abiotic and biotic stresses and fungal pathogens in plants. However, no OLPs have been functionally elucidated in poplar. Here, we report an osmotin-like protein designated PdOLP1 from Populus deltoides (Marsh.). Expression analysis showed that PdOLP1 transcripts were mainly present in immature xylem and immature phloem during vascular tissue development in P. deltoides. We conducted phenotypic, anatomical, and molecular analyses of PdOLP1-overexpressing li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…These results indicate that PtoMYB055 indeed participates in the formation of wood in poplar as a positive regulator. In addition, Li et al reported that PdOLP1, an Osmotin-like protein in poplar, is a negative regulator of secondary wall biosynthesis and PtoBLH8 and PtoWRKY40 repress the transcriptional activation of its promoter [39]. PtoMYB055 also might regulated the secondary cell wall biosynthesis via activating or repressing other regulators, such as PdOLP1.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that PtoMYB055 indeed participates in the formation of wood in poplar as a positive regulator. In addition, Li et al reported that PdOLP1, an Osmotin-like protein in poplar, is a negative regulator of secondary wall biosynthesis and PtoBLH8 and PtoWRKY40 repress the transcriptional activation of its promoter [39]. PtoMYB055 also might regulated the secondary cell wall biosynthesis via activating or repressing other regulators, such as PdOLP1.…”
Section: Discussionmentioning
confidence: 99%
“…KNAT 2/6b, one member of the class I KNOX genes, inhibited the xylem differentiation by regulating NAC TF in poplar [ 60 ]. The overexpression of PdOLP1 , an osmotin-like protein gene in poplar, caused a reduction in the radial width and cell layer number in xylem and phloem zones, and downregulated expression of genes involved in lignin biosynthesis, and in the fibers and vessels of xylem cell walls [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…These proteins accumulate under stress conditions that result in the compartmentalization of ions or solutes and initiate anti-pathogen activities (Kumar et al, 2015). To date, the genes that encode osmotins and OLPs have been isolated from various plant species, which are known to exhibit multiple functions to enhance stress tolerance (Le et al, 2018;Li et al, 2020).…”
Section: Role Of Osmotin In Abiotic Stress Tolerancementioning
confidence: 99%